Pharmaceutico-Analytical Study of Vishatinduka Taila (International Journal of Ayurveda and Pharma Research, 2022)
Vishatinduka Tailam is mentioned in context of Vataroga nidhanalakshana chikitshaadhyana of Basavarajiyam text for the treatment of Sarvangasandhiasthigatavata, Amlavata, Sula, Anulomanavayu, Sthambha, Dhanurvata, Kaphajavikaras, severe painful condition of the body, etc., It is prepared with ingredients like Vishatinduka, Jambira, Aranala, Tilataila and Erandataila. It is an attempt made to validate the pharmaceutical and analytical parameters of Vishatinduka taila. Three batches of Vishatindukataila were prepared. Pharmaceutical study of batches and its standardization was done. It took five days for preparation of each batch due to presence of Aranala. Intermittent cooling was done. At the end of Taila preparation, mustard brown coloured oil was obtained and strong odour present. All Sneha siddhi lakhanas were observed and the loss was approximately 10% in all the three batches of Taila. To establish standards of Vishatinduka Taila, physicochemical and chromatographical methods were performed. The results found are acid value 12.344mg/KOH/g, peroxide value 5Meq/kg, Density 0.932g/cm3, Specific gravity 0.932, pH 4.5+/_0.3, Loss on drying 0%, Refractive index 73.5+/_0.2% brix, saponification value 112.22mg KOH/1g and Total fatty matter 95.4%. Physicochemical test was done in first and second month also results obtained. In HPTLC evaluation variable number of spots are visualized. It showed the presence of four phytoconstituents.